2020
DOI: 10.1128/jvi.00032-20
|View full text |Cite
|
Sign up to set email alerts
|

Murine Leukemia Virus P50 Protein Counteracts APOBEC3 by Blocking Its Packaging

Abstract: Apolipoprotein B editing, catalytic subunit 3 (APOBEC3) family members are cytidine deaminases that play important roles in intrinsic responses to retrovirus infection. Complex retroviruses like HIV-1 encode the viral infectivity factor (Vif) protein to counteract APOBEC3 proteins. Vif induces degradation of APOBEC3G and other APOBEC3 proteins and thereby prevents their packaging into virions. It is not known if murine leukemia virus (MLV) encodes a Vif-like protein. Here we show that the MLV P50 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…A recent study by this group also suggested that M-MLV and F-MLV encode a second viral protein that antagonizes APOBEC restriction [312]. Previous experiments suggested that alternative splicing of genomic MLV RNA leads to two proteins, p50 and p60, which are translated from the Gag AUG and CUG initiation codons, respectively [313].…”
Section: Betaretroviruses and Deamination-independent Apobec Activitymentioning
confidence: 96%
“…A recent study by this group also suggested that M-MLV and F-MLV encode a second viral protein that antagonizes APOBEC restriction [312]. Previous experiments suggested that alternative splicing of genomic MLV RNA leads to two proteins, p50 and p60, which are translated from the Gag AUG and CUG initiation codons, respectively [313].…”
Section: Betaretroviruses and Deamination-independent Apobec Activitymentioning
confidence: 96%
“…Murine leukemia virus (MLV) possesses two mechanisms to overcome the restriction by mouse A3. On the one hand, its P50 protein, produced from an alternatively spliced gag RNA [ 145 , 146 ], prevents mouse A3 packaging by interacting with its C-terminus CD2 domain, but impacts neither its degradation nor its deaminase activity [ 147 ]. Considering that the C-terminus of mouse A3 is necessary for its incorporation into viruses, it is not surprising that P50 binding to this domain affects A3 packaging.…”
Section: Degradation-independent Inhibition Of Apobec3 Proteins By Other Virusesmentioning
confidence: 99%
“…Unlike the degradative impact of Vif on A3G, g-gag antagonizes mA3 indirectly by stabilizing the viral core and preventing A3 access to the viral DNA/RNA by shielding the viral reverse transcriptase complex [ 167 ]. Apart from g-gag, mA3-mediated restriction of MLV replication is also be counteracted by the viral p50 protein, produced by alternative splicing of gag , which interacts with mA3 and prevents its packaging into newly produced virions [ 168 , 169 ].…”
Section: Retroviral Restriction Factorsmentioning
confidence: 99%